FALLING DOWN THE KINGDOM: CULTURE AND TRADITION ON FAMILY BUSINESS SUCCESSION - Husien, Susminingsih; Kirana, Kusuma Chandra; Hermuningsih, Sri (Review of Behavioral Aspect in Organizations and Society, 2019)
This paper aims to analyze the intersection between culture, behavior, and family in determining the new leader of family business. Organizationally, the culture of family has a significant role in the founder's willingness to hand over his business to someone who is undoubtedly considered the best. This paper uses a qualitative approach where the appropriate theoretical foundation is applied to explain the succession of family business. However, observation method is used in order to obtain the facts of family business succession of batik industry in Pekalongan City, Indonesia. Meanwhile, the sociology and psychology approach used to analyze these facts; therefore, the succession process can be explained correctly. This paper provides several important results of family business succession in Pekalongan City, Indonesia. The succession tends to be carried out in several stages; therefore, the process runs smoothly, i.e., the successor improves his/her ability in managing the business, and then its predecessor reduces their responsibility. Further, the succession process consists of two models, namely planned and unplanned models, where they have their strengths and weakness. We believe some factors influence the succession process, such as motivation, commitment, and dependence of predecessor and successor.